2022
DOI: 10.1007/s00269-021-01173-3
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure behaviour and atomic-scale deformation mechanisms in inyoite, CaB3O3(OH)5·4H2O

Abstract: The compressional behaviour of inyoite, ideally CaB3O3(OH)5•4H2O, has been studied by an insitu high-pressure single crystal X-ray experiment, at the ESRF large scale facility, up to 19.80(5) GPa. Inyoite undergoes a first-order phase transition to inyoite-II, bracketed between 8.25(5) and 8.86(5) GPa, with a large volume discontinuity (ΔV⁓7.5%). The structure of the high-pressure polymorph has not been solved due to a significant decrease in the number of Bragg reflections.The isothermal bulk modulus (KV0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition, these minerals release sodium, when dissolved into the paste, which can activate harmful reactions for the durability of Portland cement concretes. In the framework of a long-term project to select new B-bearing aggregates, as potential substituents of borax and ulexite in cement concretes, we have re-investigated the crystal chemistry, chemical stability and low/high-temperature and pressure behaviour of a series of natural borates: colemanite (CaB 3 O 4 (OH) 3 •H 2 O, Lotti et al 2017a,b;2019), kernite (Na 2 B 4 O 6 (OH) 2 •3H 2 O, Comboni et al 2020a;Gatta et al 2020), kurnakovite (MgB 3 O 3 (OH) 5 •5H 2 O, Gatta et al 2019;Pagliaro et al 2021) and inyoite (Ca 2 B 6 O 6 (OH) 10 •8H 2 O, Comboni et al 2021a). This study extends our investigation to meyerhofferite, which is a Na-free borate, ideally CaB 3 O 3 (OH) 5 •H 2 O (or Ca 2 B 6 O 6 (OH) 10 •2H 2 O), and contains up to 46.7 wt% B 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these minerals release sodium, when dissolved into the paste, which can activate harmful reactions for the durability of Portland cement concretes. In the framework of a long-term project to select new B-bearing aggregates, as potential substituents of borax and ulexite in cement concretes, we have re-investigated the crystal chemistry, chemical stability and low/high-temperature and pressure behaviour of a series of natural borates: colemanite (CaB 3 O 4 (OH) 3 •H 2 O, Lotti et al 2017a,b;2019), kernite (Na 2 B 4 O 6 (OH) 2 •3H 2 O, Comboni et al 2020a;Gatta et al 2020), kurnakovite (MgB 3 O 3 (OH) 5 •5H 2 O, Gatta et al 2019;Pagliaro et al 2021) and inyoite (Ca 2 B 6 O 6 (OH) 10 •8H 2 O, Comboni et al 2021a). This study extends our investigation to meyerhofferite, which is a Na-free borate, ideally CaB 3 O 3 (OH) 5 •H 2 O (or Ca 2 B 6 O 6 (OH) 10 •2H 2 O), and contains up to 46.7 wt% B 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, above the phase transition, the +10% volume increase of the Li tetrahedron is coupled with a triplication of its 𝜎 2 (Table 2), reflecting a major increase in the Li tetrahedron deformation. Contrary to the other hydrous borates studied so far, the high-pressure phase transition of jadarite does not lead to an increase in the coordination of any boron site (e.g., 21,26,41,42 ). Furthermore, in other studies (e.g., meyerhofferite, colemanite, kernite, kurnakovite, ulexite, etc.…”
Section: P-induced Structure Deformation and Comparison Between The L...mentioning
confidence: 61%
“…Contrary to the other hydrous borates studied so far, the high‐pressure phase transition of jadarite does not lead to an increase in the coordination of any boron site (e.g., 21,26,41,42 ). Furthermore, in other studies (e.g., meyerhofferite, colemanite, kernite, kurnakovite, ulexite, etc.…”
Section: Resultsmentioning
confidence: 99%
“…In both the experiments, crystals did not recover after the phase transition. This was the most destructive phase transition observed in hydrated borates to date (e.g., Comboni et al, 2020bComboni et al, , 2022b, since the number of observed reflections was barely enough to properly index the diffraction pattern of the high-pressure polymorph, inderborite-II, which was found to be metrically monoclinic. The space group has not unambiguously determined.…”
Section: Discussionmentioning
confidence: 99%